Escolarização e anarquismo: modernização educacional e educação dos corpos na perspectiva libertária da Escola Moderna de Barcelona (anos finais do século XIX e início do século XX) - Pedro Henrique Prado da Silva (2021)
The objective of this research was to investigate the educational conceptions and practices directed to the bodies of infancy in the anarchist ideology, between the final years of the XIX century and the beginning of the XX century, versifying the analysis about the Modern School at Barcelona (1901–1906). Before the contingencies which are usually nominated as modernity and the possibilities of their effects on a school with anarchist tendencies, the research aimed to comprehend the ways in which the Modern School inventoried and operated with a set of knowledges, artifacts, systems and objectives introduced in their prescriptions and practices that, at some level, were directed to the bodies of the scholars, so as to identify the ruptures, distancing and permanencies, as well as the tension caused in the construction of their experiences regarding the context in which it was inserted. Using an English historiographic tradition, especially Edward Palmer Thompson, the investigation is carried out with the concepts of experience and culture commonly present through the work of such author. For the empirical analysis it was organized documentary fonts, mainly, originated and produced by the Modern School, such as school manuals and its official bulletin, notwithstanding, building a broader documentary corpus in which integrate fonts from other nature: legislatures, journals, pedagogic magazines, congress minutes, specialized books etc. It was verified that the Modern School at Barcelona, although showing some similarities with other experiences and ideas that circulated in that moment about the education of bodies, it also promoted a pedagogic proposition that unveiled the contradictions behind the social project of expansion of capitalism and of the republican democracy, giving proper meanings and sense to its educational experiences, from that incorporated a singular itinerary to edify another social project.